PENERAPAN KONSELING RATIONAL EMOTIVE THERAPY DENGAN TEKNIK REINFORCEMENT UNTUK MENGOPTIMALKAN MOTIVASI BELAJAR DI PONDOK PESANTREN AN-NUUR - Hikmah, Dwi Sylviatun; Sucipto, Sucipto; Kiswantoro, Arista (Jurnal Muria Research Guidance and Counseling (MRGC), 2024)
This research originates from the problems of students at the An-nuur Islamic boarding school who experience a decrease in learning motivation. Decreased motivation to learn originates from irrational thinking, resulting in irrational behavior. Learning motivation is the urge or desire to do something to achieve a goal. To help with these students' problems, researchers provide counseling services using a rational emotive therapy approach using reinforcement techniques. The goal of rational emotive therapy counseling is to help clients free themselves from illogical ways of thinking or ideas and replace them with logical ways of thinking. Providing reinforcement techniques aims to provide reinforcement in all decisions and changes made by the counselee. This strengthening is expected to help the counselee in making changes.